Calcifying Cystic Odontogenic Tumor (CCOT-Gorlin tumor) of the alveolar part of the mandible - a case report - Gnatek, Adrian; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2018)
Odontogenic tumor – like lesions are rarely occurring pathological processes in jawbones. The article presents a case of a 39-year-old-patient that had been treated surgically because of Gorlin tumor of alveolar part of mandible. Clinical examination showed alveolar ectasia in the region of the tumor in mandible. Due to patient’s mental impairment taking any X-rays and surgery photographic documentation was impossible.